Peptide P5 (residues 628–683), comprising the entire membrane proximal region of HIV-1 gp41 and its calcium-binding site, is a potent inhibitor of HIV-1 infection - Clavel François; Labrosse Beatrice; Alfsen Annette; Tudor Daniela; Yu Huifeng; Bomsel Morgane (Retrovirology, 2008)
Abstract The membrane proximal region (MPR) of the transmembrane subunit, gp41, of the HIV envelope glycoprotein plays a critical role in HIV-1 infection of CD4+ target cells and CD4-independent mucosal entry. It contains continuous epitopes recognized by neutralizing IgG antibodies 2F5, 4E10 and Z13, and is therefore considered to be a promising target for vaccine design. Moreover, some MPR-derived peptides, such as T20 (enfuvirtide), are in clinical use as HIV-1 inhibitors. We have shown that an extended MPR peptide, P5, harbouring the lectin-like domain of gp41 and a calcium-binding site, is implicated in the interaction of HIV with its mucosal receptor. We now investigate the potential antiviral activities of P5 and other such long MPR-derived peptides. Structural studies of gp41 MPR-derived peptides using circular dichroism showed that the peptides P5 (a.a.628–683), P1 (a.a.648–683), P5L (a.a.613–683) and P7 (a.a.613–746) displayed a well-defined α-helical structure. Peptides P5 inhibited HIV-1 envelope mediated cell-cell fusion and infection of peripheral blood mononuclear cells by both X4- and R5-tropic HIV-1 strains, whereas peptides P5 mutated in the calcium binding site or P1 lacked antiviral activity, when P5L blocked cell fusion in contrast to P7. Strikingly, P5 inhibited CD4-dependent infection by T20-resistant R5-tropic HIV-1 variants. Cell-cell fusion studies indicated that the anti-HIV-1 activity of P5, unlike T20, could not be abrogated in the presence of the N-terminal leucine zipper domain (LZ). These results suggested that P5 could serve as a potent fusion inhibitor.